Limited scope for reproductive senescence in wild populations of a short-lived fish - Vrtílek, Milan; Žák, Jakub; Blažek, Radim; Polačik, Matej; Cellerino, Alessandro; Reichard, Martin (Die Naturwissenschaften, 2018)
Senescence in wild populations was long considered negligible but current evidence suggests that it is widespread in natural populations of mammals and birds, affecting the survival and reproductive output of older individuals. In contrast, little is known about reproductive senescence in species with asymptotic growth that can keep increasing their reproductive output as they grow older and larger. Using a cross-sectional study, we tested age-related decline in fecundity and relative allocation to reproduction in five wild populations of an annual killifish, Nothobranchius furzeri (Cyprinodontiformes). We did not detect any decline in absolute female egg production over their short lifespan in the wild. Relative fecundity (egg production controlled for female body mass) tended to decrease with age. This effect was driven primarily by a single population that survived 17 weeks, almost twice as long as the median persistence of the other four study populations. There was no decrease in relative ovary mass while in males, relative testes mass actually increased with age. Intra-population variation in relative ovary mass increased in older females suggesting heterogeneity in individual trajectories of female reproductive allocation. Overall, we demonstrate that annual killifish do not experience significant age-related decline in reproductive functions during their very short lifespan in the wild despite the marked deterioration of gonad tissue detected in captivity.
Keywords: Reproduction; Cyprinodontiformes; divoká zvířata; rozmnožování; gonády; Reproductive ageing; Female; Longevity; Plasticity; stárnutí; zvířata; Aging; Animals, Wild; Gonads; ženské pohlaví; Male; Population heterogeneity; dlouhověkost; Turquoise killifish; Animals; mužské pohlaví; Gene by environment interaction